Coupled coincidence point theorems for (φ; ψ)-contractive mixed monotone mapping in partially ordered metric spaces - Phakdi Charoensawan (2018)
In this paper, we proved some coupled coincidence and coupled common fixed point theorem for such nonlinear contractive mappings in partially ordered complete metric spaces. The main results of this paper are generaliza-tion of the main results of Alotaibi and Alsulami (Coupled coincidence points for monotone operators in partially ordered metric spaces, Fixed Point Theory and Applications 2011, 2011:44). © 2013 by the Mathematical Association of Thailand. All rights reserved.